Conservatório Maestro Paulino (1971-2014) no contexto da formação do campo cultural em Ponta Grossa (PR): possibilidades e limites de promoção da cultura musical como elemento de humanização - Vendrami, Georgeana Lanzini (2015)
This study analyzes political and social-historical determinations that characterize Maestro Paulino Martins Alves Conservatory (CMP) in Ponta Grossa, Parana, from 1971 to 2014. The objectives of the research were: 1) understand the nature and the educational and cultural dimension of the CMP from the empirical particularities that characterize its internal movement and its external intervenients; 2) problematize the possibilities and limits of the CMP in giving access to musical culture as an element of humanization of senses of the population who attends there, having in mind the molds of its genesis, from its development and its concretion in the city of Ponta Grossa living. The arguments of this thesis is mainly based on Marx‟s theorical and methodological principles, especially in the ontological dimension of the esthetic and social thinking developed by Marx and Engels that recognize the art as one of the ways of object of the social being. According to this perspective, arguments formulated by Lukács about the art are taken into account, the process of the constitution of the man in its whole and its role in the human emancipation. This research involved relative theoretical studies on the literature review and its documental analysis and empirical studies through interviews and questionnaires aimed to candidates, students, applicants, teachers and directors of the CMP, public administrators of the culture and cultural agents from the city of Ponta Grossa, and they were analyzed from a qualitative approach. The results of the research allow us to say that, regardless all limitations on material, political and human behalf on the CMP as a public institution of musical teaching, the educational process developed promotes a resizing of the conceptions, expectations, objectives and knowledge about music, art and culture of the students who were there, which contributes to the legitimation of a different social position in relation to the development of the human senses of the amount of people from Ponta Grossa who attends this place.